Emergence percentage and speed of rootstocks for citriculture in south of Brazil. - MARQUES, L. O. D. (2019)
ABSTRACT.The fact that Brazilian citriculture has focused on few rootstocks poses several phytosanitary risks to the culture and has made genetic improvement programs develop hybrid genotypes to be used as novel alternatives. This study aimed at evaluating the behavior of 42 different rootstocks regarding their emergence percentage and speed in weather conditions experienced in the extreme south of Brazil. Seeds of hybrids developed by the Citrus Genetic Improvement Program (PMG Citros) at the Embrapa Mandioca e Fruticultura (PMG Citros) and cultivars from other citrus growing regions were sown in conical tubes filled with commercial substrate in May 2017. A thoroughly randomized design with 4 replicates, each composed of 45 sampling units, was employed. Emergence percentage and emergence speed of every genotype were evaluated and the ones with the highest emergence percentage of seedlings and the ones with the most precocious emergence were identified. All genotypes completed seedling emergence 98 days after sowing. Seeds of Trifoliata, TSKC × CTSW-041 and TSKC × CTSW-025 had the highest values of seedling emergence whereas the highest emergence speed indexes were exhibited by genotypes Trifoliata and lemon tree 'Cravo'.